Music and mathematics in primary education. Development of knowledge and skills concerning magnitude features = Muzyka i matematyka w edukacji wczesnoszkolnej. Rozwój wiedzy i umiejętności dotyczących cech wielkościowych - Łuczak, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to present the possibilities of developing knowledge and skills related to magnitude characteristics based on integrating music and mathematics in primary education. Early childhood education specialists agree that creative combinations of various issues are essential to support and stimulate harmonious development. The first part presents information on the relationship between music and mathematics, which was noticed already in antiquity. The following focuses on examples and possibilities of shaping mathematical concepts in quantitative features through various musical activities at individual stages.
Keywords: primary education; early childhood education; music; mathematics; edukacja wczesnoszkolna; muzyka; matematyka; cechy wielkościowe